A PROJECT EVALUATION IN SURAKARTA (A Case Project of Order and Built in Taman SumberAsri Housing) - DIAN ARUMNINGSIH DIAH P. (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2006)
The Housing business is an effort done by developers to gain profits from the offered investments. In developing housing business, there are two functions that the developers should carry on; the busiÂness and technical function. The Business function means that every cost should mutually affect incomes or profits. The tecnical function means that developers should build houses with their facilities for the consumers. This research purposes to evaluate time and cost at the Development of Order and Build Housing in Taman Sumber Asri Housing Project in Surakarta. This research used Critical Path Method (CPM), Curve S and Bar Chart. At the Development of Order and Build housing process, there hapÂpened accelerations at elapsed time in which the project was conducted, so that the project retained the cost reduction from the planed budget initially. The concept of result value, or the term known as earned value method, which generally can be ident ivied by the integrity of cost and time technique, has the basic concept of the progress evaluation at the progress of the process infield, with 2 variables scales; the time and cost variable. The research result showed the difference of cost at Rp. 2,182,445, -, retained from the initial budget ofRp. 107,193,550 - (Housing type 80/140. the land price and land tax were excluded) into Rp. 105, Oil, 105. Based on time estimations, it was calculated the time for building the house was 15,673 weeks. According to the plan, the housing would be finished in 16 weeks, so that there happened an acceleration of 0.327 weeks from the initial plan. For the totally 5 years in finishing the project, in 2years 5 months, the project have been accomplished that it underwent time acceleration of 2 years and 7 month, or 31 months. From the project cost view, the project gained profits as much as Rp 1,797,046,572,-